Selecting a model of unmanned aerial vehicle to accept it for military purposes with regard to expert data - Alimpiev, Andrey; Berdnik, Polina; Korolyuk, Natalia; Korshets, Elena; Pavlenko, Maxim (Eastern-European Journal of Enterprise Technologies, 2017)
The issue of equipping Armed Forces with modern unmanned aerial vehicles and accepting them into service remains unresolved. At present, the needs of Armed Forces of Ukraine in unmanned aerial vehicles have not been clearly identified, as well as the approaches regarding the choice of particular models. Present article proposes to select a model of armament based on the set of basic indicators (criteria) that may have quantitative and qualitative nature. We substantiate the necessity to predict the values of indicators under conditions of nonstochastic uncertainty. It is noted that should the research utilize statistics, then the task of predicting the given characteristics could be solved under conditions of stochastic uncertainty. In this case, it is necessary to take into account the assumption that the set of factors, which defined statistical significance of TTC, remains unchanged over the predicted time period. Under such assumption, long-term prediction of the TTC values cannot be considered satisfactory. It is obvious that the prediction of TTC values of UAV samples is considered under conditions of nonstochastic uncertainty based on the setting of appraisal and processing expert data. We proposed a decomposition of problem into hierarchy that reflects the content of multi-criteria optimization problem, in this case, it is characterized by a fuzzy description of the predicted values of basic UAV TTC, which have distinctly expressed quantitative and qualitative nature and are measured in appropriate magnitudes. An appraisal was performed to determine the predicted values of each characteristics of UAV. When processing expert data, values for each of the quantitative characteristics are represented by a fuzzy triangular number. Regarding the indicators of qualitative nature, we examined relevant linguistic variables. According to the method of hierarchy analysis, we carried out a comparative assessment of the indicators' significance. In order to obtain generalized indicators for the priority UAV model, the principle of synthesis is proposed.